Background Stress Inventory: Developing a Measure of Understudied Stress. (26th November 2013) - Terrill, Alexandra L.; Gjerde, Jill M.; Garofalo, John P.
Abstract Background stress is an understudied source of stress that involves both ambient stress and daily hassles upon which new stressors are superimposed. To date, an accurate measure of the background stress construct has not been available. We developed the Background Stress Inventory, a 25‐item self‐report measure that asks respondents to indicate how distressed they have felt over the past month and the majority of the past year across five domains: financial, occupation, environment, health and social. Seven hundred seventy‐two participants completed the paper‐and‐pencil measure; the sample was randomly split into two separate subsamples for analyses. Exploratory factor analysis suggested five factors corresponding to these domains, and confirmatory factor analysis showed acceptable global fit (X2(255) = 456.47, comparative fit index = 0.94, root mean square error of approximation = 0.045). Cronbach's alpha (0.89) indicated good internal reliability. Construct validity analyses showed significant positive relationships with measures of perceived stressfulness (r = 0.62) and daily hassles (0.41), p's < 0.01. Depressive symptoms (0.62) and basal blood pressure (0.21) were both significantly associated with background stress, p's < 0.01. The importance of the proposed measure is reflected in the limited research base on the impact of background stress. Systematic investigation of this measure will provide insight into this understudied form of chronic stress and its potential influence on both psychological and physical endpoints. Copyright © 2013 John Wiley & Sons, Ltd.